Supporting business processes through human and IT factors: a maturity model. Issue 4 (2nd July 2018) - Mamoghli, Sarra; Cassivi, Luc; Trudel, Sylvie
Abstract : Purpose: The purpose of this paper is to assist organizations in the assessment of both information technology (IT) and human factors required to support their business processes (BPs) by taking into account the interdependence and alignment of these factors, rather than considering them independently. Design/methodology/approach: A design science research methodology was followed to build a maturity model (MM) enabling this assessment. The proposed design process is composed of four steps: problem identification, comparison of 19 existing MMs in business process management (BPM), iterative model development, and model evaluation. The last two steps were specifically based on three research methods: literature analysis, case studies, and expert panels. Findings: This paper presents a MM that assigns a maturity level to an organization's BPs in two assessment steps. The first step evaluates the level of sophistication and integration of the IT systems supporting each BP, while the second step assesses the alignment of human factors with the technological efforts. Research limitations/implications: The research was conducted with SMEs, leading to results that may be specific to this type of organization. Practical implications: Practitioners can use the proposed model throughout their journey toward process excellence. The application of this model leads to two main process improvement scenarios: upgrading the sophistication and integration of the software technologies in support of the processes, and improving the cohesion of the resources the organization already owns (human and IT resources). Originality/value: The proposed MM constitutes a first step in the assessment of the interdependence between the factors influencing BPM.